2013
DOI: 10.5455/medarh.2013.67.256-259
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Use of Benzodiazepines in the Frequency Falls in the Elderly

Abstract: Out of 376 respondents were significantly more women 242 (64%) compared to 134 men (46%), the decline has been seen 128 (34%) were taking benzodiazepine 216 (57%) of the respondents, the most commonly used benzodiazepine is bromazepam and a positive correlation was found between the use of benzodiazepines and frequency of falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
3
0
5
Order By: Relevance
“…CNS effects, such as cognitive impairment and sedation, as well as drug interactions play a significant role in elderly patients [ 33 , 35 , 37 ]. Of particular concern is the increased risk of falls in elderly patients receiving benzodiazepine treatment [ 38 , 39 ], with potentially life-threatening consequences.…”
Section: Discussionmentioning
confidence: 99%
“…CNS effects, such as cognitive impairment and sedation, as well as drug interactions play a significant role in elderly patients [ 33 , 35 , 37 ]. Of particular concern is the increased risk of falls in elderly patients receiving benzodiazepine treatment [ 38 , 39 ], with potentially life-threatening consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The association between benzodiazepines use and falls risk, or fall-related complications (i.e., injuries, fracture) has been reported by several researchers in the last two decades (Chang et al, 2011, Rossat et al, 2011, de Vries et al, 2013, Softic et al, 2013, Ballokova et al, 2014). One of the earlier studies in this area demonstrated an increased hospitalization rate from falls within 4 weeks after the first BDZs prescription, especially in older adults (Neutel et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…Quando a substância em questão é capaz de provocar um efeito de grande intensidade e de gerar uma modificação importante da personalidade, é considerada psicotrópica. 36 As substâncias psicotrópicas têm sido usadas com diversos fins ao longo da história.…”
Section: Hemitartarato De Zolpidemunclassified